Papers - Mill Design - Mill Design for Labor Economy (T. P. 1997, Min. Tech., May 1946, with discussion) - Norman Weiss (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1947)
The need for more efficient utilization of labor in the metal-mining industry has been the subject of several recent editorials in the mining press, and one attractive possibility for such improvement lies in the designing of future milling plants particularly with economy of manpower in mind. We are accustomed to think of mill design as the selection and coordinated arrangement of process equipment, but if labor is to be efficiently utilized it must be given early consideration in planning the new mill. There are three good reasons for economizing in labor: (I) to reduce costs, not only in the form of wages but also in housing, hospital, welfare, and other obligations that a company accepts when a new man is added to the payroll; (2) to prepare for recurrent periods of manpower shortage, during which a well-designed plant can manage to get along with skeleton crews; (3) because a milling plant that must depend upon an inordinately large labor force for its operation and maintenance is certain to be inefficient in other respects, for many of the shortcomings in design that make necessary the excessive use of labor are generally not corrected merely by having too many men. A simple example of this is a poorly designed ore-feeding system : if this is inadequate to the extent that one man must be constantly unclogging feed chutes, it may help the situation to put two men or three at this task instead of one, but the feed rate will still be inconstant. First of the factors that affect labor saving is the location of the mill. This is often determined by transportation costs alone, and as a result the mill may be placed close to the mine regardless of the nature of the terrain. The designer must then adapt his layout to the conditions, favorable or not. This happens often at small properties, where capital investment may seem more important than operating expense. In most instances, however, a mill site carefully selected for the advantages it gives the designer in laying out the plant is the most economical in the long run, even if it involves a slight increase in cost of ore haulage. Given some freedom of choice, the design engineer may be able to find just the piece of ground that provides the proper gradient for the needs of the flowsheet, permits installation of essential yards and trackage, and perhaps supplies an excellent site for a tailing dam. Further justification for having placed the mill not too close to the mine sometimes emerges only years later as an opportunity to treat ores from other properties. When it is known from the beginning that the new mill will serve a number of scattered mines, a free choice of mill site is naturally stimulated. The most important single factor in limiting the labor requirements of a mill is its materials-handling system for bring-